2016
DOI: 10.1097/ico.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Intraocular Pressure Changes After Anterior Chamber Air Fill in Descemet Membrane Endothelial Keratoplasty

Abstract: Adequate inferior iridectomy greatly alleviates the risk and severity of acute IOP rises after nearly full anterior chamber air tamponade in DMEK. Standard IOP adjustment at the end of DMEK surgery with postoperative IOP monitoring especially in the first 2 postoperative hours is advisable when there is no postoperative default air release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 26 publications
(26 reference statements)
0
42
0
4
Order By: Relevance
“…The data have been collected prospectively within the Cologne DMEK database , using the RED‐Cap (Research Electronic Data Capture) electronic data capture tool, which is a secure, web‐based application designed to support data capture for research studies (Stanzel et al. ). The study was conducted in adherence to the tenets of the Declaration of Helsinki and was approved by the local Institutional Review Board (No.…”
Section: Methodsmentioning
confidence: 99%
“…The data have been collected prospectively within the Cologne DMEK database , using the RED‐Cap (Research Electronic Data Capture) electronic data capture tool, which is a secure, web‐based application designed to support data capture for research studies (Stanzel et al. ). The study was conducted in adherence to the tenets of the Declaration of Helsinki and was approved by the local Institutional Review Board (No.…”
Section: Methodsmentioning
confidence: 99%
“…Pilocarpine 1% eye drops were applied three times a day as long as the anterior chamber was filled with air or gas covering the pupil's bottom margin. Patients were instructed to keep a strict supine position postoperatively, at least for three days with only bathroom privileges under continuous monitoring of IOP 21. IOP was measured at least four times a day.…”
Section: Methodsmentioning
confidence: 99%
“…It is also controversial how long the tamponade should be left in the anterior chamber. Many surgeons prefer a tamponade release after a short period of complete anterior chamber filling to mitigate the risk of acute IOP elevations [7-10]. Stanzel et al [10] reported on an intensified postoperative IOP observation within 24 h and found mostly mild IOP increases in 40 cases with retained tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgeons prefer a tamponade release after a short period of complete anterior chamber filling to mitigate the risk of acute IOP elevations [7-10]. Stanzel et al [10] reported on an intensified postoperative IOP observation within 24 h and found mostly mild IOP increases in 40 cases with retained tamponade. The authors concluded that adequate inferior iridotomy greatly alleviated the risk and severity of acute IOP rises after nearly full anterior chamber air tamponade in DMEK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation